Curriculum Assessment on Navigation 1 among Students, Instructors and Administrators - Bringas, Rey David; Felias, Victor; Arellano, Jhon Paul; Ebarle, Cm Maximino; Mamogay, Reen David Karll; Nisperos, Nikko James; Puebla, Jee Mark; Remitar, Rey (JPAIR Institutional Research, 2024)
The Curriculum Assessment on Navigation 1 at the Merchant Marine Academy of Caraga Inc. is crucial for ensuring the competence and safety of future mariners. This quantitative research involves maritime students in their 2nd and 3rd years, instructors, and administrators as respondents. The study aims to evaluate the Navigation 1 curriculum, focusing on students’ study habits, academic performance, teachers’ profiles, instructional delivery modalities, and perceptions of the curriculum by students, administrators, and instructors. Data collection includes questionnaires and statistical analyses like frequency distribution, weighted mean, and chi-square tests. Initial findings indicate a high level of agreement and positive perceptions across various aspects of the curriculum, with an overall weighted mean of 3.72. The study suggests that the Navigation 1 curriculum effectively meets its objectives. Future research should assess the long-term effectiveness of the curriculum by tracking graduates’ performance, gathering industry feedback, and integrating new technologies to enhance student preparation for real-world navigation challenges.